(3JYQja GdMjQGf Yf cjajI Ndb GdEfSGfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj Ndb GdEfSGf ef Wjf Ke LYd fSdg ef SdGdI ef eGA egjf (B... (3ebOeI, GYde Cf GdPj MOGfj Edi JCdja gPG GdeDda eG QCjJg ef cdGe dHYV YdeGFfG GdeJbOejf aj eYfi GdMOjK GdfHhj (B... (3ef YQa faSg abO YQa QHgs
(3BNQgG (B:s
(3BNQgG(B: (3hdG JcJe GdHZV SGYI hGMOI hGdYRdI fhaQ GdYQV hfTQ GdaGbI hJQaY fbd GdecGaCI heG GMJfc CMO bW EdG CMH GdNdhI hGdYRdI, Gddge CLYdfG eef CMH GdNdhIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdWHs